2022
DOI: 10.54996/anatolianjem.1020308
|View full text |Cite
|
Sign up to set email alerts
|

Sağlık Çalışanlarına Yönelik Şiddetin Pandemi ile İlişkisi

Abstract: Aim:To evaluate the effect of the pandemic process on the white code notifications in our hospital by examining the data of the white code call system, which is carried out in order to prevent violence against healthcare workers.Material and Methods: A total of 212 White code notifications evaluated due to date, time, gender of the health worker who was exposed, duty, hospital unit where the incident occurred, the reason for the violence, type of violence, legal aid status received after the White Code notific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 16 publications
0
4
0
1
Order By: Relevance
“…When the gender exposed to violence was evaluated in the study, no statistically significant difference was found between male and female gender, unlike other studies conducted in Turkey. [6] In the 5-year analysis, there was no significant difference between the areas where the white code was given. However, we were surprised that other units such as the laboratory and radiology ranked second in terms of frequency, after the place where contact with patients and their relatives is easiest, such as the emergency department.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…When the gender exposed to violence was evaluated in the study, no statistically significant difference was found between male and female gender, unlike other studies conducted in Turkey. [6] In the 5-year analysis, there was no significant difference between the areas where the white code was given. However, we were surprised that other units such as the laboratory and radiology ranked second in terms of frequency, after the place where contact with patients and their relatives is easiest, such as the emergency department.…”
Section: Discussionmentioning
confidence: 91%
“…[8] When the duties of health workers are compared, it is observed that doctors are more exposed to violence, parallel to previous studies. [6] but with a more serious intensity and difference. This situation is in parallel with the data in crowded countries such as India and China.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Çalışmamızda ayrıca COVID-19 pozitif hastalar ile çalışan hemşirelerin daha fazla sözlü şiddete maruz kaldıkları belirlenmiş, bu durum istatistiksel olarak anlamlılık ifade etmiştir. Sağlık çalışanlarına yönelik şiddet, çalışanların fizyolojik/ psikolojik iyilik hali, iş motivasyonu ve sağlık bakım kalitesini olumsuz yönde etkilemektedir (Aygün & Metin, 2022). Brezilya' da yapılan bir çalışmada sağlık çalışanlarının başta hastalar olmak üzere, hasta yakını ve iş arkadaşları tarafından sözlü şiddete maruz kaldıkları belirlenmiş, hastalık çalışma süresinde meydana gelen artışın şiddet oluşma eğilimini de artırdığı saptanmıştır (Bitencourt et al, 2021).…”
Section: Discussionunclassified